2009
DOI: 10.1093/eurheartj/ehp055
|View full text |Cite
|
Sign up to set email alerts
|

Risks of cardiovascular events and effects of routine blood pressure lowering among patients with type 2 diabetes and atrial fibrillation: results of the ADVANCE study

Abstract: Atrial fibrillation is relatively common in type 2 diabetes and is associated with substantially increased risks of death and cardiovascular events in patients with type 2 diabetes. This arrhythmia identifies individuals who are likely to obtain greater absolute benefits from blood pressure-lowering treatment. Atrial fibrillation in diabetic patients should be regarded as a marker of particularly adverse outcome and prompt aggressive management of all risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
1
13

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(126 citation statements)
references
References 24 publications
2
106
1
13
Order By: Relevance
“…Cukrzyca i AF często współistnieją ze względu na zwią-zek z innymi czynnikami ryzyka [277][278][279][280][281][282][283]. Cukrzyca jest czynnikiem ryzyka udaru mózgu i innych powikłań AF [284].…”
Section: Cukrzycaunclassified
“…Cukrzyca i AF często współistnieją ze względu na zwią-zek z innymi czynnikami ryzyka [277][278][279][280][281][282][283]. Cukrzyca jest czynnikiem ryzyka udaru mózgu i innych powikłań AF [284].…”
Section: Cukrzycaunclassified
“…Microalbuminuria has also been linked to AF in a population of more than 20,000 hypertensive patients [5]. In the Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation (ADVANCE) study, which included more than 11,000 patients with type 2 diabetes, Du et al showed that patients with AF had higher levels of blood pressure and albuminuria [6]. Finally, studying 2,671 type 2 diabetes patients originating from the SURDIAGENE (Survie, Diabete de type 2 et Genetique) and DIAB2NEPHROGENE (Diabete de type 2, Nephropathie et Genetique) cohorts, our group showed that albuminuria was strongly linked to prevalent AF and prolonged P-wave duration [7].…”
Section: Af Atrial Fibrillationmentioning
confidence: 99%
“…В исследовании ADVANCE было проанализировано, на-сколько МА влияет на смертность и сердечно-сосудистый риск у больных с СД [29]. Напомню, что ADVANCE является ран-домизированным факторильным исследованием, включающим в себя 11 140 больных СД2 в возрасте 55 лет и старше, имеющих по крайней мере 1 дополнительный фактор риска сердечно-сосудистых заболеваний Больные основной группы получали фиксированную дозу периндоприла и индапамида, которая по-степенно увеличивалась до максимальной дозы периндоприла в 8 мг/сут.…”
Section: сахарный диабетunclassified